PSYCHOLOGICAL MECHANISM UNDERLYING THE MANNERS OF CHINESE TOURISTS AT ENTERTAINMENT EVENTS (Proceedings of the International Conference on Hospitality and Tourism Management, 2023)
Chinese tourists are increasing in number around the world. However, despite their positive economic impact, they negatively affect the residents and business operators at their destinations in terms of poor manners according to the e-WOM (word of mouth) Japanese travel web site and interviews conducted in Thailand. Although measures have been taken, these have been limited to the separation of Chinese tourists and compulsory rules concerning manners, and there has been no study involving adequate communication with the tourists themselves. Therefore, it was attempted to understand the Chinese psychological mechanism for service companies to be able to communicate effectively withChinese tourists. Through a questionnaire-based experiment to investigate adult Chinese prosocial behavior at entertainment events, the empirical validity of a developmentalpsychology-based hypothesis concerning the effect of attachment style was tested. As a result, it was found that the positiveness of the view of others has a positive effect onconsidering the perspectives of others, on an empathic interest in others, and on an expectation of others having a good reputation. However, only the empathic interest in others and the expectation of others having a good reputation positively affects prosocial behavior. Consequently, the mechanism of prosocial behavior of adult Chinese consumerswas identified, which will enable business operators to build a more effective communication strategy with such consumers.